Pituitary apoplexy in pregnancy: A case series and literature review. (December 2015) - Grand'Maison, Sophie; Weber, Florence; Bédard, Marie-Josée; Mahone, Michele; Godbout, Ariane
Background: Severe headache during pregnancy is a challenging condition that may rarely imply endocrine disturbances. Rapid recognition of pituitary apoplexy is needed to improve pregnancy outcome. Objective: To review and compare maternal and fetal outcomes after pituitary apoplexy. Methods: Four cases of pituitary apoplexy during pregnancy in our centre are reported and literature review covering the past 54 years was performed. Results: In the four cases presented and the 33 reported in the literature, most women presented with severe headaches and systemic symptoms. Overall, 42% were treated surgically, 31% received bromocriptine or cabergoline and 61% were given hormone replacement. No major obstetrical complication was reported and all babies were healthy. Conclusion: Pituitary apoplexy is a rare cause of sudden and severe headache during pregnancy. Rapid identification of this condition with potentially associated endocrine disturbances is important to ensure maternal and fetal well-being. A multidisciplinary team approach seems to reduce morbidity and mortality.